UMPSA organises UMPSA Strategic Plan 2026-2028 Engagement Session with students - Rosidah, Hassan (UMPSA, 2024)
PEKAN, 13 June 2024 – The Centre for Strategic Management and Quality (PPSK), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) held an Engagement Session on the Development of the UMPSA 2026-2028 Strategic Plan (UMPSA28) with Students at DK3, Faculty of Electrical and Electronic Engineering Technology (FTKEE), Pekan recently.